Respuesta :

Answer:

Proved

Step-by-step explanation:

Given

[tex]1+5+9+...+[4(n-1)+1]+[4n+1] = (n+1)(2n+1)[/tex]

[tex]n \geq 1[/tex]

Required

Prove by induction

[tex]1+5+9+...+[4(n-1)+1]+[4n+1] = (n+1)(2n+1)[/tex]

Increment n by 1 on both sides

[tex]1+5+9+...+[4(n-1)+1]+[4n+1]+[4(n+1)+1] = (n+1+1)(2(n+1)+1)[/tex]

Simplify the right hand side

[tex]1+5+9+...+[4(n-1)+1]+[4n+1]+[4(n+1)+1] = (n+2)(2n+2+1)[/tex]

[tex]1+5+9+...+[4(n-1)+1]+[4n+1]+[4(n+1)+1] = (n+2)(2n+3)[/tex]

Group the left hand side

[tex](1+5+9+...+[4(n-1)+1]+[4n+1])+[4(n+1)+1] = (n+2)(2n+3)[/tex]

Recall that

[tex]1+5+9+...+[4(n-1)+1]+[4n+1] = (n+1)(2n+1)[/tex] ----[Given]

So; Substitute [tex](n+1)(2n+1)[/tex] for [tex]1+5+9+...+[4(n-1)+1]+[4n+1][/tex] on the left hand side

[tex](n+1)(2n+1)+[4(n+1)+1] = (n+2)(2n+3)[/tex]

Open All Brackets

[tex]2n^2 + n + 2n + 1 + 4n + 4 + 1 = 2n^2 + 3n + 4n + 6[/tex]

Collect Like Terms

[tex]2n^2 + n + 2n + 4n+ 1 + 4 + 1 = 2n^2 + 3n + 4n + 6[/tex]

[tex]2n^2 + 7n+ 6 = 2n^2 + 7n + 6[/tex]

Notice that the expression on both sides are equal;

Hence, the given expression has been proven